2020
DOI: 10.1101/2020.04.12.038000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic Architecture of Cells in Tissues (GeACT): Study of Human Mid-gestation Fetus

Abstract: Highlights• Genomic Architecture of Cells in Tissues (GeACT) data for human mid-gestation fetus • Determining correlated gene modules (CGMs) in different cell types by MALBAC-DT • Measuring chromatin open regions in single cells with high detectability by METATAC • Integrating transcriptomics and chromatin accessibility to reveal key TFs for a CGM Summary By circumventing cellular heterogeneity, single cell omics have now been widely utilized for cell typing in human tissues, culminating with the undertaking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…High-throughput single-cell analysis has proved to be a valuable strategy for understanding the functional mechanisms of cells and tissues (7, 29). However, identifying functional gene expression programs from large-scale single-cell dataset has been challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High-throughput single-cell analysis has proved to be a valuable strategy for understanding the functional mechanisms of cells and tissues (7, 29). However, identifying functional gene expression programs from large-scale single-cell dataset has been challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, single-cell transcriptomics study has been widely used to distinguish different types of cells. Apart from cell typing, high-precision single-cell transcriptomics can also measure correlations in steady-state gene expression (6, 7). However, proteins, rather than mRNAs, are direct executers of most biological processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these ‘basal programs’ may not necessarily represent real expression programs, they can also come from technical noise. Genes having protein products that interact with each other tend to have similar functions and co-expression patterns ( 16 ). To determine the genuine co-expression pattern shared among batches (or the featured expression module characterizing a give cell/tissue type), we incorporated PPI network information into ICAnet, and used the ‘basal programs’ to score PPI.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, using PPIs as the backbone to discover gene-expression modules in scRNA-seq analyses is now feasible. Previous studies have revealed that genes with PPIs showed co-expression trends at the RNA level ( 16 , 103 ), suggesting that integrating PPI information into scRNA-seq data analyses could be beneficial. In practice, we performed multiple simulations and statistical tests to demonstrate the importance of incorporating PPI networks into cell clustering and module interpretations of scRNA-seq data (see Supplementary Notes, Sections 2 and 3 in the Supplementary Materials).…”
Section: Discussionmentioning
confidence: 99%